The impact of pharmaceutical care interventions for medication underuse in older people: a systematic review and meta-analysis - Meid, Andreas; Lampert, Anette; Burnett, Alina; Seidling, Hanna; Haefeli, Walter E. (British journal of clinical pharmacology, 2015)
Aims The aim of the present study was to conduct a meta-analysis of controlled trials assessing the impact of pharmaceutical care interventions (e.g. medication reviews) on medication underuse in older patients (≥65 years). Methods The databases MEDLINE and EMBASE were searched for controlled studies, and data on interventions, patient characteristics and exposure, and outcome assessment were extracted. Risk of bias was assessed using the Cochrane Collaboration's ‘risk of bias’ table. Results from reported outcomes were synthesized in multivariate random effects meta-analysis, subgroup meta-analysis and meta-regression. Results From 954 identified articles, nine controlled studies, mainly comprising a medication review, were included (2542 patients). These interventions were associated with significant reductions in the mean number of omitted drugs per patient (estimate from six studies with 1469 patients: - 0.44; 95% confidence interval -0.61, -0.26) and the proportion of patients with ≥1 omitted drugs (odds ratio from eight studies with 1833 patients: 0.29; 95% confidence interval 0.13, 0.63). The only significant influential factor for improving success was the utilization of explicit screening instruments when conducting a medication review (P = 0.033). Conclusion Pharmaceutical care interventions, including medication reviews, can significantly reduce medication underuse in older people. The use of explicit screening instruments alone or in combination with implicit reasoning is strongly recommendable for clinical practice.